2015
DOI: 10.1542/peds.2014-2377
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Versus Clonidine for Neonatal Abstinence Syndrome

Abstract: OBJECTIVE: The study goal was to determine whether clonidine treatment of neonatal abstinence syndrome (NAS) would result in a better neurobehavioral performance compared with morphine.METHODS: This pilot study prospectively enrolled infants $35 weeks' gestational age admitted for treatment of NAS. After informed consent was obtained, infants were randomized to receive morphine (0.4 mg/kg per day) or clonidine (5 mg/kg per day) divided into 8 doses. A 25% dose escalation every 24 hours was possible per protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 43 publications
0
64
0
Order By: Relevance
“…10,11,12 Clinicians have treated NAS with a variety of opioid preparations. 49 In addition to opioid therapy, several other medications are in use as adjunctive therapy, such as clonidine and phenobarbital. 1,4,45 In a recent pilot study by Bada et al, 49 infants with NAS were treated with morphine (0.4 mg/kg per day) versus clonidine (5 mg/kg per day) divided into 8 doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,12 Clinicians have treated NAS with a variety of opioid preparations. 49 In addition to opioid therapy, several other medications are in use as adjunctive therapy, such as clonidine and phenobarbital. 1,4,45 In a recent pilot study by Bada et al, 49 infants with NAS were treated with morphine (0.4 mg/kg per day) versus clonidine (5 mg/kg per day) divided into 8 doses.…”
Section: Discussionmentioning
confidence: 99%
“…49 In addition to opioid therapy, several other medications are in use as adjunctive therapy, such as clonidine and phenobarbital. 1,4,45 In a recent pilot study by Bada et al, 49 infants with NAS were treated with morphine (0.4 mg/kg per day) versus clonidine (5 mg/kg per day) divided into 8 doses. Treatment duration was significantly longer for the morphine group (n = 15; median 39 days) than for the clonidine group (n = 16; median 28 days) (P = .02), showing effects comparable to those of our pilot study (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether single-agent clonidine treatment is as effective as morphine in the treatment of NAS, a pilot randomized double-blind single center study was conducted [93]. A total of 31 infants ≥35 weeks’ gestational age were enrolled in the study and randomized to receive morphine (0.4 mg/kg per day) or clonidine (5 ug/kg per day) divided into 8 doses.…”
Section: Symptomatic Carementioning
confidence: 99%
“…Additionally, NNNS scores improved with clonidine but not morphine and one-year motor, cognitive, and language scores did not differ between the two groups. The investigators concluded that clonidine single agent therapy is as effective as morphine used for the treatment of NAS [93]. Since this was a small pilot study, a large randomized multicenter trial is necessary.…”
Section: Symptomatic Carementioning
confidence: 99%
“…Clonidine is an α 2 ‐adrenoceptor agonist commonly used as an antihypertensive agent (Nishina, Mikawa, Shiga, & Obara, ). In opioid withdrawal, enhanced noradrenergic activity is observed owing to the loss of opiate inhibition on noradrenergic neurons (Bada et al, ). Through stimulation of α 2 ‐adrenergic receptors, clonidine decreases noradrenergic neurotransmission and thus relieves withdrawal symptoms (Bada et al, ; Langer, Cavero, & Massingham, ; Nishina et al, ).…”
Section: Introductionmentioning
confidence: 99%